Advances in Liquid Absorbents for CO2 Capture: A Review - Rosli, Aishah; Ahmad, Abdul Latif; Lim, Jit Kang; Siew, Chun Low (Universiti Sains Malaysia, 2017)
The emission of greenhouse gases, especially carbon dioxide (CO2) has been a major concern worldwide for several years now, as it causes global warming. Even though various CO2 capture technologies have been researched, liquid absorption is widely considered a popular and effective method for the removal of CO2. For this reason, the choice of absorbent used to absorb the greenhouse gas is of vital importance. This article provides a brief overview of various liquid absorbents that have been investigated for this purpose, both in absorption columns and membrane contactor settings. Research journals currently available show that the usage of common amines and their combinations have been investigated, as well as several alternatives, additions and enhancements to existing liquid absorbents to improve the capture of CO2 and these are discussed in this article.